Sanidad interna de árboles de Cedrelinga cateniformis (Ducke) ducke aplicando técnica no destructiva en el campo experimental el Dorado-Inia, Loreto-Perú, 2022 - Mozombite Yay, Yoly Polastrih (2023)
The study was carried out in the "El Dorado" Experimental Field, Iquitos Nauta highway km25, belonging to the "San Roque" Agrarian Experimental Station of the National Institute of Agrarian Innovation (INIA), in Cedrelinga Cateniformis (Ducke) Ducke plantations of different ages, with the objective of evaluating the dasometry, morphology and internal health of C. cateniformis trees of 18, 26, 33 years and their contribution to commercial forest species in plantations, the inventory and georeferencing of each tree to be evaluated was carried out, To measure the internal health of the stem of the trees, the acoustic tomograph with the ArbSonic3D program was used to obtain knowledge of the internal state of the plantations. The results indicate that the 18-year-old C. cateniformis plantation has a tree health of 98.33%, showing an internal state in good condition with a very low percentage of rot, likewise the 26-year-old plantation is 98, 00% Arborea health and finally 80, 41 tree health in the 33-year-old plantation of C. Cateniformis, showing the existence of rot and hollows in the evaluated trees, the analysis of variance carried out gives a significant result and is confirmed by the test of Tukey, regarding the evaluation in the Kolmorogrov-Smirnov test, in qualification it is No parameters in commercial height and basal area.